2011
DOI: 10.1088/0004-637x/739/1/52
|View full text |Cite
|
Sign up to set email alerts
|

The Atacama Cosmology Telescope: Cosmological Parameters From the 2008 Power Spectrum

Abstract: We present cosmological parameters derived from the angular power spectrum of the cosmic microwave background (CMB) radiation observed at 148 GHz and 218 GHz over 296 deg 2 with the Atacama Cosmology Telescope (ACT) during its 2008 season. ACT measures fluctuations at scales 500 < < 10,000. We fit a model for the lensed CMB, Sunyaev-Zel'dovich (SZ), and foreground contribution to the 148 GHz and 218 GHz power spectra, including thermal and kinetic SZ, Poisson power from radio and infrared point sources, and cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
455
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 362 publications
(498 citation statements)
references
References 129 publications
39
455
3
1
Order By: Relevance
“…In the final 9-year WMAP analysis no significant running was seen using WMAP data alone, with dn s /dln k = −0.019 ± 0.025 (68% confidence; Hinshaw et al 2012. Combining WMAP data with the first data releases from ACT and SPT, Hinshaw et al (2012) found a negative running at nearly the 2σ level with dn s /dln k = −0.022 ± 0.012 (see also Dunkley et al 2011 andKeisler et al 2011 for analysis of ACT and SPT with earlier data from WMAP). The ACT 3-year release, which incorporated a new region of sky, gave dn s /dln k = −0.003 ± 0.013 ) when combined with WMAP 7 year data.…”
Section: Scale Dependence Of Primordial Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the final 9-year WMAP analysis no significant running was seen using WMAP data alone, with dn s /dln k = −0.019 ± 0.025 (68% confidence; Hinshaw et al 2012. Combining WMAP data with the first data releases from ACT and SPT, Hinshaw et al (2012) found a negative running at nearly the 2σ level with dn s /dln k = −0.022 ± 0.012 (see also Dunkley et al 2011 andKeisler et al 2011 for analysis of ACT and SPT with earlier data from WMAP). The ACT 3-year release, which incorporated a new region of sky, gave dn s /dln k = −0.003 ± 0.013 ) when combined with WMAP 7 year data.…”
Section: Scale Dependence Of Primordial Fluctuationsmentioning
confidence: 99%
“…In the Standard Model, N eff = 3.046, due to noninstantaneous decoupling corrections (Mangano et al 2005). However, there has been some mild preference for N eff > 3.046 from recent CMB anisotropy measurements (Komatsu et al 2011;Dunkley et al 2011;Keisler et al 2011;Archidiacono et al 2011;Hinshaw et al 2012;Hou et al 2014). This is potentially interesting, since an excess could be caused by a neutrino/anti-neutrino asymmetry, sterile neutrinos, and/or any other light relics in the Universe.…”
Section: Constraints On N Effmentioning
confidence: 99%
See 1 more Smart Citation
“…Further theoretical investigation (Scott & White 1999;Haiman & Knox 2000) was stimulated by the detection of the infrared background in the COBE data (Puget et al 1996;Fixsen et al 1998), and the detection of bright "sub-millimetre" galaxies in SCUBA data (Hughes et al 1998). Subsequently, the clustering has been detected at 160 microns , at 250, 350 and 500 microns by the Balloon-borne Large Aperture Submillimeter Telescope (BLAST, Viero et al 2009;Hajian et al 2012) and at 217 GHz by SPT and ACT (Hall et al 2010;Dunkley et al 2011). Recent Planck measurements of the CIB (Planck Collaboration XVIII 2011) have extended the measurements at 217 GHz, 353 GHz, and 545 GHz to larger scales, and recent Herschel measurements (Viero et al 2013) have improved on the BLAST measurements and extended them to smaller angular scales.…”
Section: Clustered Power From Unresolved Point Sourcesmentioning
confidence: 99%
“…We develop a model for these foregrounds, designed to allow the Planck likelihood to be combined with high resolution data from the Atacama Cosmology Telescope (ACT) and the South Pole Telescope (SPT). We combine frequencies and model unresolved foregrounds in a physical way, as in e.g., Shirokoff et al (2011);Dunkley et al (2011);Reichardt et al (2012), performing component separation at small scales at the power spectrum level. On large scales, < 50, Galactic contamination is more significant.…”
Section: Introductionmentioning
confidence: 99%